Activity-based costing of canned and processed foods businesses in Thailand: effects on organizational development, business competitiveness and corporate success - Ussahawanitchakit, Phaprukbaramee (Business: Theory and Practice, 2017)
This study aims at investigating the relationships among activity-based costing, organizational development, business competitiveness, and corporate success of canned and processed foods businesses in Thailand. In this study, 142 canned and processed foods businesses in Thailand are the samples of the study. Structural equation model (SEM) was employed to test the research relationships. The research results indicate that activity-based costing positively leads to organizational development and business competitiveness. Also, organizational development positively relates to business competitiveness and corporate success while business competitiveness positively affects corporate success. In summary, activity-based costing plays a significant role in determining, driving and explaining firm outcomes. Accordingly, firms need to pay attention to the development and utilization of activity-based costing through the provision of competencies, capabilities, resources, and assets to its implementation. To verify the current study, future research may need to search for activity-based costing’s dimensions and components, collect data from different populations and countries and apply regression analysis, partial least squared and path analysis to prove the relationships.